Sustainability and Cultural Capital: An Opportunity to Improve the Built Environment - Conte, Emilia (European Journal of Sustainable Development, 2017)
The quest for sustainable development in the building sector has greatly improved the sustainability of buildings through energy efficiency and use of renewable resources. However, green buildings are not the only objects in the built environment, and environmental sustainability is not the only aspect to be pursued for sustainable development. The author claims that, to improve an overall real sustainability, we need to introduce the cultural capital, which is now disregarded, in the interpretation of the built environment so that physical and temporal scales can be reconnected and continuity of the process of development can be ensured. Starting from this premise, the paper is organised into three main sections: the first represents two key interpretations of the built environment; the second discusses the limits of such interpretations through the example of sustainable buildings; the third explains why the cultural capital can be considered an opportunity to improve sustainability of the built environment. Keywords: Overall sustainability; Built environment; Cultural capital; Sustainable buildings.